Electrical characteristics of ALD‐deposited Al2O3 thin films on p‐type germanium substrates. Issue 1 (29th November 2012) - Botzakaki, M.; Kerasidou, A.; Xanthopoulos, N.; Skarlatos, D.; Kennou, S.; Ladas, S.; Georga, S. N.; Krontiras, C. A.
Abstract The electrical behaviour of Al/Al2O3/p‐Ge MOS capacitors, with 10 nm oxide thickness, has been studied in the temperature range between 130 K and 330 K. The ALD method for the Al2O3 deposition has been used. C‐V and G‐f measurements reveal high values of the density of interfacial traps Dit, suggesting the presence of leakage currents. Conductivity mechanisms for the leakage currents have been studied, on the basis of J‐V characteristics of the structure as a function of temperature. In the measured voltage region (0‐2.5 V), tunneling is proposed as the dominant mechanism. Specifically, as the applied field increases, Fowler‐Nordheim mechanism gradually contributes to the, observed at low fields, Ohmic conduction (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)